2004
DOI: 10.1007/bf02351013
|View full text |Cite
|
Sign up to set email alerts
|

Feature selection of stabilometric parameters based on principal component analysis

Abstract: This study addresses the challenge of identifying the features of the Centre of pressure (COP) trajectory that are most sensitive to postural performance, with the aim of avoiding redundancy and allowing a straightforward interpretation of the results. Postural sway in 50 young, healthy subjects was measured by a force platform. Thirty-seven stabilometric parameters were computed from the one-dimensional and two-dimensional COP time series. After normalisation to the relevant biomechanical factors, by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(151 citation statements)
references
References 32 publications
7
132
1
4
Order By: Relevance
“…The results obtained confirm our hypothesis that prolonged wearing of unstable shoes increases postural control performance, demonstrated by a decrease of the most representative CoP displacement parameters (Collins & De Luca, 1993;Maurer & Peterka, 2005;Pavol, 2005;Rocchi, et al, 2004), and decreased postural control system error, demonstrated by the adaptation of the RM and TR components (Zatsiorsky & Duarte, 2000), more marked in the unstable shoe condition. However, our results failed in demonstrating a decreased co-activation command and increased reciprocal activation command as a training effect.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results obtained confirm our hypothesis that prolonged wearing of unstable shoes increases postural control performance, demonstrated by a decrease of the most representative CoP displacement parameters (Collins & De Luca, 1993;Maurer & Peterka, 2005;Pavol, 2005;Rocchi, et al, 2004), and decreased postural control system error, demonstrated by the adaptation of the RM and TR components (Zatsiorsky & Duarte, 2000), more marked in the unstable shoe condition. However, our results failed in demonstrating a decreased co-activation command and increased reciprocal activation command as a training effect.…”
Section: Discussionsupporting
confidence: 85%
“…A 95% confidence ellipse for each trial was estimated to enclose approximately 95% of the CoP motion points in the 2D domain. These parameters were selected as they were demonstrated to be sensitive to postural performance and efficiency (Rocchi et al, 2004).…”
Section: Antagonist Co-activationrf/(bf+gm) Pair=mentioning
confidence: 99%
“…Particular attention was given to weight, height, base of support area, feet-opening angle and maximum foot width during between-subject comparisons. In 2004 (Rocchi et al 2004) to promote standardization in quantitative posturography, the same authors suggested that if no normalization is undertaken, it is essential to constrain the foot position in such a way as to reduce inter-subject variability of base of support measurements. Furthermore, they underlined the need to align properly the reference frame of the subject with the reference frame of the platform.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the constructs differ between these measures. The center of pressure variables used in this study reflect both the balance control processes necessary to maintain stance and movement of the entire body's center of mass [14]. Previous studies have shown that even when standing with eyes open, PwMS exhibit a larger center of pressure sway area [4,30], greater sway velocity [3,30], and greater RMS of sway than nondisabled controls [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, we used the composite score from the Sensory Organization Test (SOT) as generated by commercially available posturography devices and we extracted the raw center of pressure signal from each trial of the SOT and calculated root mean square (RMS), range, total sway area, and mean velocity for the resultant sway path. Analyses of these center of pressure variables have been shown to most effectively characterize different aspects of postural sway [14][15]. For example, sway area reflects the effectiveness of, or the stability achieved by, the postural control system and mean velocity reflects the amount of regulatory activity associated with this level of stability [15][16].…”
Section: Introductionmentioning
confidence: 99%